Exome sequencing identifies genes for socioeconomic status in 350,770 individuals - Xin-Rui Wu; Liu Yang; Bang-Sheng Wu; Wei-Shi Liu; Yue-Ting Deng; Ju-Jiao Kang; Qiang Dong; Barbara J. Sahakian; Jian-Feng Feng; Wei Cheng; Jin-Tai Yu (Proceedings of the National Academy of Sciences, 2025)
Socioeconomic status (SES) is a critical factor in determining health outcomes and is influenced by genetic and environmental factors. However, our understanding of the genetic structure of SES remains incomplete. Here, we conducted a large-scale exome study of SES markers (household income, occupational status, educational attainment, and social deprivation) in 350,770 individuals. For rare coding variants, we identified 56 significant associations by gene-based collapsing tests, unveiling 7 additional SES-associated genes ( NRN1 , CCDC36 , RHOB , EP400 , NCAM1, TPTEP2-CSNK1E , and LINC02881 ). Exome-wide single common variant analysis revealed nine lead single-nucleotide polymorphisms (SNPs) associated with household income and 34 lead SNPs associated with EduYears, replicating previous GWAS findings. The gene–environment correlations had a substantial impact on the genetic associations with SES, as indicated by the significantly increased P values in several associations after controlling for geographic regions. Furthermore, we observed the pleiotropic effects of SES-associated genetic factors on a wide range of health outcomes, such as cognitive function, psychosocial status, and diabetes. This study highlights the contribution of coding variants to SES and their associations with health phenotypes.